Media Digital Sebagai Pendukung Pelayanan Misi Gereja - Gabby Naca Stevany; Frans Hisar Mangatur Silalahi (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research aims to describe and analyze the role of digital media as a supporter of Church mission services. Digital media is utilized as one of the facilities for church services and digital media is also a challenge for every church. An optimistic attitude is a real attitude that needs to be instilled and carried out by every church as an effort to improve and achieve service goals and quality. Descriptive qualitative method is a research method through literature research used by the author in conducting research. Literature studies are used by the author as a target to provide a sense of awarness and optimism for the progress of media in the world and the church in seeing and making an opportunity not a threat. The results of the discussion and research provide input to a pastor and every congregational leader in a church regarding what things must be improved and improved optimally to utilize digital media that is and continues to develop in supporting church services and spreading the gospel throughout the world.